IMPLEMENTATION OF BAR COOPERATION WITH OTHER DEPARTMENTS AT GRAND ELITE HOTEL PEKANBARU - Fadli, Arya Ramadhani; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Cooperation is a relationship between two or more people who carry out a process to achieve a common goal where each party will provide a solution, different thoughts and perceptions and give rise to a process of bargaining with each other. In hotel operations, of course, it requires effective inter-departmental cooperation relationships so that operations can run smoothly. The bar is one part of the department that has a cooperative relationship with all hotel departments. This research was conducted in January-May 2023 located at the Grand Elite Hotel Pekanbaru. The purpose of this study is to know the role of the Bar towards other departments, know the form of Bar Cooperation with other departments to improve service quality, and constraints what was found during Bar operations at Grand Elite Hotel Pekanbaru. Data were collected using interview, observation and documentation techniques. The results showed that each department plays an important role in bar operations and has a close cooperative relationship so that operational activities run smoothly. Keywords: Cooperation, Hotel, Bar